2021
DOI: 10.1080/14760584.2021.1932475
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of convalescent plasma for SARS-CoV-2 prophylaxis and treatment in immunocompromised and vulnerable populations

Abstract: Introduction : The ongoing SARS-CoV-2 pandemic is a serious threat for the health of immunocompromised patients. Among neutralizing antibody-based therapeutics, convalescent plasma containing polyclonal anti-SARS-CoV-2 immunoglobulins has promising results in both congenital and iatrogenic immunodeficiencies in oncohematological and transplant patients. Areas covered : This article discusses case reports, case series and controlled studies detailing the efficacy of conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 74 publications
0
28
0
1
Order By: Relevance
“…There is growing evidence from cohort studies and case-series, that CP therapy in frail immunosuppressed individuals, unable to mount effective anti-SARS-CoV-2 antibody responses, reduces viral load and improves clinical symptoms, even when given late after initial diagnosis (20)(21)(22)(23)(24)(25). Accordingly, these findings suggest that the administration of plasma with high neutralizing antibody titers is a safe and effective treatment for immunosuppressed patients (3,26,27).…”
Section: Introductionmentioning
confidence: 98%
“…There is growing evidence from cohort studies and case-series, that CP therapy in frail immunosuppressed individuals, unable to mount effective anti-SARS-CoV-2 antibody responses, reduces viral load and improves clinical symptoms, even when given late after initial diagnosis (20)(21)(22)(23)(24)(25). Accordingly, these findings suggest that the administration of plasma with high neutralizing antibody titers is a safe and effective treatment for immunosuppressed patients (3,26,27).…”
Section: Introductionmentioning
confidence: 98%
“…Polyclonal antibodies such as CCP are likely to offer better protection against onset of variants than monoclonal antibodies (9496): importantly, Pommeret et al showed that CCP can rescue immune escape variants emerged during treatments with bamlanivimab/etesevimab cocktail (97). Outcomes in immunocompromised patients treated with CCP have been successful in the long-term, with minimal evidence for immune escape (98).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical benefit seems absent when administered after 1 week from onset of symptoms or in patients requiring ventilation, or in those who receive CCP with a low nAb titer. Nevertheless, chronically immunosuppressed patients benefit from CCP even at later stages (98, 105, 106) : the best evidence for this scenario comes from a prospective PSM showing a halving of mortality in ICU-admitted oncohematological COVID-19 patients who received CCP (107). We note that while there have been concerns that use in immuncompromised can promote the emergence of antibody-resistant variants, such variants have emerged from massive replication in susceptible populations and not from treated patients, who in any case are isolated in hospitals where mitigation efforts to reduce transmission are employed, and are thus very unlikely to transmit their viruses further (108).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst there are many vaccines for COVID-19, this may not be an option for immunocompromised and vulnerable populations where effective therapies are needed, particularly due to being prone to more severe COVID-19 ( Focosi and Franchini 2021 ). Therefore, the results reported within presents an additional avenue applicable for both the current COVID-19 pandemic and future infectious disease threats.…”
Section: Discussionmentioning
confidence: 99%